Levels of 1,25(OH)2D3 for patients with pulmonary tuberculosis and correlations of 1,25(OH)2D3 with the clinical features of TB - Gao, Wei-Wei; Wang, Yu; Zhang, Xiang-Rong; Yin, Chun-Yang; Hu, Chun-Mei; Tian, Man; Wang, Hong-Wei; Zhang, Xia (Journal of Thoracic Disease; Vol 6, No 6 (June 26, 2014): Journal of Thoracic Disease, 2014)
Background: To determine the 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] concentrations to patients with tuberculosis (TB) and whether it influenced the patient’s clinical features. Methods: For the first part, a total of 153 healthy adults and 74 patients with pulmonary TB (PTB) were enrolled. Serum concentrations of 1,25(OH)2D3 were determined by liquid chromatography-tandem mass spectroscopy to examine the 1,25(OH)2D3 concentrations of the two groups from the peripheral blood. If there are differences between the two groups, what follow will increase the experimental group numbers to examine the relationship among the 1,25(OH)2D3 concentrations with the numbers of the lesion area, the tubercule bacilli in sputum and the CD4/CD8 ratio of T lymphocytes in the peripheral blood. Results: In the first part, the 1,25(OH)2D3 concentrations was lower in patients with TB than in those healthy adults [365.9 (SD 235.7) vs. 464.3 (SD 335.6), P